Python unit test automation : practical techniques for Python developers and testers - Pajankar, Ashwin (Apress, 2017)
This book shows readers how to automate unit testing of Python 3 code by introducing various Python 3 automation libraries, such as doctest, unittest, nose, nose2, and pytest. It also explores the important concepts in software testing and their implementation in Python 3. Hands-on knowledge of the frameworks helps readers to automate, organize, and execute their unit tests for Python 3. Knowledge of the frameworks discussed in the book is often acquired by reading source code, manuals, and posting questions on community forums. This tends to be a slow and painful process. Python Unit Test Automation will allow readers to quickly ramp up their understanding of unit test libraries for Python 3 through the practical use of code examples and exercises. All of which makes this book a great resource for software developers and testers who want to get started with unit test automation in Python 3.